Case Report: A Rare Case of Acute Anterior Myocardial Infarction Simultaneously Associated With Aortic Mural Thrombosis Due to Essential Thrombocytosis - Ye, Sheng; Xia, Wu-jie; Chen, Peng (Frontiers in Cardiovascular Medicine, 2022)
Background Essential thrombocytosis (ET) simultaneously complicated with acute myocardial infarction and aortic thrombosis is extremely rare and associated with poor outcomes. Case A 54-year-old female was admitted to our emergency department with abdominal pain for 3 h. ST-segment elevation in leads V1–V3 on electrocardiography led to the diagnosis of acute anterior myocardial infarction. Coronary angiography demonstrated total occlusion of the proximal left anterior descending artery, and the patient was treated with angioplasty and placement of a drug-eluting stent. CT angiography revealed a massive mural thrombus located in the descending aorta. Bone marrow biopsy confirmed the diagnosis of ET. The patient was successfully treated with antithrombotic therapy and hydroxyurea. Conclusion At present, the clinical diagnosis and treatment of ET complicated with acute myocardial infarction and aortic thrombosis are mostly based on literature reports. Early target vessel revascularization, antiplatelet and anticoagulant combined with cytoreductive therapy may improve the prognosis. Clinicians should consider the risk of bleeding and thrombosis and create individualized treatment strategies for these patients.